Efficacy of extended clomifene citrate regimen in comparison with gonadotropins in clomifene citrate-resistant women with polycystic ovary syndrome - Hassan, Mahmoud Fathy (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Gonadotropins are successful treatment for women with clomifene citrate (CC)-resistant polycystic ovary syndrome (PCOS). The aim of this study was to test the hypothesis that extended CC treatment may be an alternative to gonadotropins in the management of CC-resistant women with PCOS. Methods: A randomized controlled trial comprised 200 women with CC-resistant PCOS were allocated to two equal treatment groups. Patients in the CC group were given 100 mg of CC daily starting from the third day of menses for 10 days. Patients in the gonadotropins group were given follitropin-alfa according to step-up regimen starting on the 3rd day of menses. The primary outcome measure was the biochemical pregnancy rate [diagnosed by measuring serum β-human chorionic gonadotropin (β-HCG) 16-days after HCG injection] and clinical pregnancy rate (confirmed by vaginal ultrasound at six-weeks of amenorrhea). Secondary outcomes were: ovulation rate, endometrial thickness at HCG injection, and adverse drug events. Results: There were no statistically significant differences between the CC group and the gonadotropins group regarding biochemical pregnancy rates [21%, 24%; respectively, P=0.735; relative risk (RR)=0.88, 95% confidence interval (CI), 0.52-1.47], and clinical pregnancy rate [19%, 21%; respectively, P=0.86; RR=0.9, (95% CI, 0.52-1.58)]. No significant difference was displayed regarding ovulation rate, endometrial thickness at HCG, and adverse drug events. Conclusions: The extended CC regimen appears to constitute a good alternative to gonadotropins therapy in patients with CC-resistant PCOS. Further multi-center studies are needed to confirm our results and to provide more powerful evidence.